INTENSIVE STRATEGIES AND MARKET POSITION OF COMPETING FIRMS IN AN ATRACTIVE INDUSTRY - Dr. Macaulay E. Wegwu (Scholar Express Journals, 2022)
This study investigated the relationship between intensive strategies and market position of competing firms in an attractive industry. The population for the study consisted of thirty-two (32) manufacturing firms in Port Harcourt. The sample for this study consisted of 10 manufacturing firms with a total number of 80 employees made up of managers and supervisors. One research question was deemed necessary, and three (3) research hypotheses were formulated to guide the study. The data for this research was collected through primary source. The p-value was used in testing the hypotheses, while the Spearman Rank-order correlation coefficient statistical tool was adopted to test the degree of relationships between the variables under study. Findings from the study revealed that there is a positive and significant relationship between all the dimensions of intensive strategies tested (i.e. market penetration, market development and product development) and market position of the competing firms. Based on the findings, it was concluded that intensive strategies have the strengths to enhance market position of competing firms in an attractive industry.
Keywords: Attractive industry; Competing firms; Intensive Strategies; Market position